2019
DOI: 10.1111/ejss.12821
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution and stoichiometry of soil carbon, nitrogen and phosphorus along an elevation gradient in a wetland in China

Abstract: Despite extensive studies on how environmental factors influence plant nutrient distribution and stoichiometry, it remains unclear how elevation affects soil distribution and stoichiometry. Here, patterns of the spatial distribution and stoichiometry of soil carbon (C), nitrogen (N) and phosphorus (P) were studied (with 123 soil samples) along a small‐scale elevation gradient in the wetland of East Dongting Lake, China. Plant nutrient concentrations (C, N and P), soil stoichiometry (C:N, C:P and N:P ratios) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 40 publications
0
7
1
Order By: Relevance
“…In this study, the average TN concentration in the surface sediment (0-20 cm) was 1.05 ± 0.66 g kg −1 , and the average TP concentration in the surface sediment was 0.49 ± 0.15 g kg −1 , which were lower than the concentrations (TN, 1.73 ± 0.79 g kg −1 ; TP, 0.89 ± 0.12 g kg −1 ) in previous studies conducted in the littoral zone of East Dongting Lake [25]. This may be because the time of sediment sampling was spring in our study and winter in a previous study.…”
Section: Distribution Of Sediment Nitrogen and Phosphoruscontrasting
confidence: 67%
See 1 more Smart Citation
“…In this study, the average TN concentration in the surface sediment (0-20 cm) was 1.05 ± 0.66 g kg −1 , and the average TP concentration in the surface sediment was 0.49 ± 0.15 g kg −1 , which were lower than the concentrations (TN, 1.73 ± 0.79 g kg −1 ; TP, 0.89 ± 0.12 g kg −1 ) in previous studies conducted in the littoral zone of East Dongting Lake [25]. This may be because the time of sediment sampling was spring in our study and winter in a previous study.…”
Section: Distribution Of Sediment Nitrogen and Phosphoruscontrasting
confidence: 67%
“…Lakeside wetlands are subject to longer inundation time and stronger nitrogen sink than riverside wetlands, resulting in higher sediment nitrogen concentration. This phenomenon may also be attributed to the dominant plants in lakeside wetlands being more luxuriant than those in riverside wetlands, with larger biomass and more litter released nitrogen into sediments [25,40]. Meanwhile, in the surface sediments, the correlations between TN and TP on the riverside were positive, and there was no correlation between TN and TP on the lakeside of Dongting Lake.…”
Section: Distribution Of Sediment Nitrogen and Phosphorusmentioning
confidence: 98%
“…Recently, numerous studies have discussed the eco-stoichiometry of soil C, N, and P in terrestrial ecosystems (e.g., wetland, grassland, forest, and desert oasis). The results indicated that soil C:N can predict the nitrate leaching degree of forest soil, while the soil N:P ratio is able to reflect the degree of vegetation disturbance [6][7][8]. C and N levels play a decisive role in the changing process of regional soil C, N, and P eco-stoichiometric characteristics [9,10].…”
Section: Introductionmentioning
confidence: 96%
“…Compositional kriging acknowledges the constant sum and non-negativity constraints of compositional data such as fractions of soil texture [66,67]. For carbon content, the ordinary kriging method was used [68,69]. For this purpose, automatically generated variograms were adapted to the point pairs and the values were regionalized by means of the autocorrelative behavior described in this way.…”
Section: Descriptive and Spatial Statistical Analysesmentioning
confidence: 99%